Manajemen Pengelolaan Pondok Pesantren Modern Rahmatul Asri Kecamatan Maiwa Kabupaten Enrekang Dalam Menanamkan Kedisiplinan Pada Santri - Suhriati Suhriati; Muhammad Saleh; Suhartina Suhartina (Institut Agama Islam Negeri Parepare, 2021)
This study focuses on the management of the modern rahmatul asri Islamic boarding school in instilling discipline in students. The purpose of this study was to determine the management system applied at the Rahmatul Asri Modern Islamic Boarding School in instilling discipline in students. This study uses a descriptive field research that is to reveal and identify the phenomena that occur. The approach taken is a qualitative approach with the types of data used are primary and secondary data. The results showed that the level of discipline of students regarding obedience and compliance with all rules and regulations, was classified as good and the management applied in instilling discipline in students was in accordance with the concept of management. The students at the Rahmatul Asri Modern Islamic Boarding School have a friendly attitude, smile, polite, humble and understand mutual respect and respect for others. All kinds of directions that are conveyed, both written and unwritten, they are carried out on the basis of seriousness and full responsibility